Clinical features and long-term outcomes in patients under 35 years with coronary artery disease: Nested case–control study - Pablo Juan-Salvadores; Dahyr Olivas-Medina; Luis Mariano de la Torre Fonseca; Cesar Veiga; Silvia Campanioni; Francisco Caamaño Isorna; Andrés Iñiguez Romo; Víctor Alfonso Jiménez Díaz (Revista Portuguesa de Cardiologia)
Introduction and objectives: Coronary artery disease (CAD) is a globally significant cardiovascular condition, ranking among the leading causes of morbidity and mortality. CAD has been predominantly associated with advanced age and classic cardiovascular risk factors. However, over the past decades, there has been a concerning rise in its occurrence among young adults, including patients under 35 years old. The present study analyzes the clinical features and outcomes of patients aged ≤35 years with CAD, compared to two age-matched control groups. Method: A nested case–control study of ≤35-year-old patients referred for coronary angiography due to clinical suspicion of CAD. Patients were divided into three groups: patients ≤35 years with CAD, subjects ≤35 years without CAD, and young patients ≥36–40 years with CAD. Results: Of the 19 321 coronary angiographies performed at our center over 10 years, 408 (2.1%) patients were ≤40 years old, 109 patients aged ≤35 years. Risk factors that showed a relationship with the presence of CAD were smoking (OR 2.49; 95% CI 1.03–6.03; p=0.042) and family history of coronary disease (OR 6.70; 95% CI 1.46–30.65; p=0.014). The group aged ≤35 years with CAD exhibited a risk of major cardiovascular adverse events (MACE) (HR 13.3; 95% CI 1.75–100; p<0.001) than subjects ≤35 years without CAD. The probability of major adverse cardiovascular events was associated with being ≤35 years old, diabetes, dyslipidemia, and depression. Conclusion: Patients aged ≤35 exhibited a poor long-term prognosis, with a high risk of new revascularization and acute myocardial infarction during the follow-up period. Focusing on preventive measures can have a significant impact on overall prognosis. Resumo: Introdução e objetivos: A doença arterial coronária (DAC) é uma condição cardiovascular globalmente significativa, classificada entre as principais causas de morbidade e mortalidade. A DAC tem sido predominantemente associada à idade avançada e aos fatores de risco cardiovasculares clássicos. No entanto, nas últimas décadas, tem havido um aumento preocupante na sua ocorrência entre adultos jovens, incluindo pacientes com menos de 35 anos. O presente estudo analisa as características clínicas e os desfechos de pacientes com idade ≤35 anos com DAC, em comparação com dois grupos controle pareados por idade. Método: Estudo caso-controle aninhado de pacientes com idade ≤35 anos encaminhados para cineangiocoronariografia por suspeita clínica de DAC. Os pacientes foram divididos em três grupos: pacientes ≤35 anos com DAC, indivíduos ≤35 anos sem DAC e pacientes jovens ≥36-40 anos com DAC. Resultados: Das 19.321 coronariografias realizadas no nosso centro num período de 10 anos, 408 (2,1%) pacientes tinham idade ≤40 anos, sendo 109 pacientes com idade ≤35 anos. Os fatores de risco que apresentaram relação com a presença de DAC foram tabagismo (OR 2,49; IC95% 1,03-6,03; p = 0,042) e história familiar de doença coronariana (OR 6,70; IC95% 1,46-30,65; p = 0,014). O grupo com idade ≤35 anos com DAC apresentou risco de MACE (HR 13,3, IC95% 1,75-100; p < 0,001) do que indivíduos ≤35 anos sem DAC. A probabilidade de MACE foi associada a idade ≤35 anos, diabetes, dislipidemia e depressão. Conclusão: Pacientes com idade ≤35 anos apresentaram mau prognóstico a longo prazo, com alto risco de nova revascularização e enfarte agudo do miocárdio durante o período de seguimento. O foco em medidas preventivas pode impactar significativamente o prognóstico geral.